Effect of Existential Group Therapy on the Quality of Sexual Life in Infertile Men\'s Spouses - samira ghorbani; Shahrbanoo Salehin; Ali Mohamad Nazari; Seyedeh Solmaz Talebi; Afsaneh Keramat (مراقبت پرستاری و مامایی ابن سینا)
Background and Objective: Infertility leads to a crisis in people's lives that can have many psychological consequences, and one of these consequences is the reduction of the quality of sexual life. Since the spouses of infertile men are as stressed as infertile women in many aspects, including sexual life, the present research aimed to investigate the effect of existential group therapy on the quality of sexual life of women who have dealt with male factor infertility. Materials and Methods: The present study followed a randomized controlled clinical trial from 2020-2021 on 96 women aged 20-45 with male-caused infertility. The samples were randomly divided into intervention and control groups. The data collection tool included a demographic questionnaire and a questionnaire on the quality of sexual life. The intervention was carried out in eight 90-minute sessions per week based on the existential group therapy counseling model. The data were collected before and after the intervention and analyzed using the SPSS (version 25) software. It is noteworthy that the level of significance was lower than 0.05. Results: Following the intervention, the quality of sexual life score in the intervention group was 67.42±17.83, indicating a statistically significant improvement compared to the pre-intervention scores and the control group (P<0.001). The analysis of the mean difference in the quality of sexual life scores between the two time points for the intervention and control groups revealed a significant difference (P<0.001). Conclusion: Existential group therapy counseling is effective in improving the quality of sexual life in women faced with male-factor infertility. Due to the effectiveness of this method, it is recommended to be used in counseling in infertility centers.